2011
DOI: 10.1089/gtmb.2010.0178
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Pathogenesis of Endometriosis; Toll-Like Receptor-4 A896G (D299G) Polymorphism: A Novel Explanation

Abstract: TLR4 A896G polymorphism (rs4986790) is a functional polymorphism resulting in hypo-responsiveness of the receptor, thus resulting in peritoneal inflammation. The molecular microenvironment becomes favorable for the endometrial cells to adhere to the peritonium, thereby resulting in the initiation of endometriosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 20 publications
2
11
0
Order By: Relevance
“…20 Recent data reveal an association between Toll-like receptor-4 A896G (D299G) polymorphism and endometriosis. 21 This polymorphism is functional, resulting in peritoneal inflammation that is favorable for the endometrial cells in the initiation of endometriosis.…”
Section: Genetics Of Endometriosismentioning
confidence: 99%
“…20 Recent data reveal an association between Toll-like receptor-4 A896G (D299G) polymorphism and endometriosis. 21 This polymorphism is functional, resulting in peritoneal inflammation that is favorable for the endometrial cells in the initiation of endometriosis.…”
Section: Genetics Of Endometriosismentioning
confidence: 99%
“…The D299G polymorphism has also been linked to Boutonneuse fever (27), RSV infections in infants and young children (28, 29), HIV-associated tuberculosis (30, 31), Crohn’s disease (32), ulcerative colitis (33), endometriosis (34), and tonsillitis (35). Human subjects carrying the T399I polymorphism either exhibit a milder LPS-hyporesponsive phenotype or do not manifest it at all (36).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a TLR-4 polymorphism associated with hypo-responsiveness of the receptor may result in peritoneal inflammation. Thus, endometrial cells tend to adhere to the peritoneum, a condition that may induce the initiation of endometriosis 11. We found that PRRs other than TLR-3 and TLR-4 are involved in immune reactions in patients with endometriosis of the peritoneal cavity.…”
Section: Discussionmentioning
confidence: 79%